The evolution of urban regime theory: the challenge of conceptualization - Mossberger, Karen; Stoker, Gerry (2001)
Urban regime theory came to prominence with the publication of Clarence Stone's study of Atlanta in 1989, although earlier work by Fainstein and Fainstein (1983) and Elkin (1987) has also been influential. Since then, regime analysis has been extensively used to examine urban politics both inside North America and beyond. The authors argue that the wide use of regime analysis is a recognition of its value and insights but that some applications have stretched the concept beyond its original meaning to the point that the concept itself runs the risk of becoming meaningless and a source of theoretical confusion. By sifting through the extensive literature applying regime theory, the authors reestablish the core components of the concept and identify the key fields where it has made a contribution. It is suggested that regime analysis has helped considerably in reorienting the power debate in North America and in facilitating the analysis of politics beyond the formal institutions of the government outside North America. - Reproduced
Keywords: Urban development